Development of a First Peoples-led cultural capability measurement tool: A pilot study with midwifery students. Issue 3 (June 2017) - West, Roianne; Wrigley, Somer; Mills, Kyly; Taylor, Kate; Rowland, Dale; Creedy, Debra K.
Abstract: Background: Midwives have a central role in closing the gap in health inequalities between Australias' First Peoples and other childbearing women. The Aboriginal and Torres Strait Islander Health Curriculum Framework (The Framework) identifies five core cultural capabilities (respect, communication, safety and quality, reflection and advocacy) to foster culturally safe health care. Aim: To use a decolonising, First Peoples-led approach to develop and validate a tool to measure the development students' cultural capabilities. Method: A pre- post intervention design was used. Development of the Cultural Capability Measurement Tool followed a staged process which centred on First Peoples' knowledges. This process included: item generation, expert review; a pilot, test-retest; and psychometric testing (reliability, factor analysis and construct validity). All third year midwifery students (n = 49) enrolled in a discrete First Peoples health course were invited to complete the survey pre and post course. Findings: A response rate of 77.5% (n = 38/49) pre-course and 30.6% (15/49) at post-course was achieved. The tool demonstrated good internal reliability (Cronbach alpha = .89–.91). Principal component analysis with varimax rotation produced a five-factor solution. A paired samples t-test revealed a significant increase from pre-course (mean 93.13, SD 11.84) to post-course scores (mean = 100.53, SD 7.54) (t (14) = −2.79, p = .014). Conclusion: A First Peoples approach was critical to tool development and conceptual validity. The 22 item Cultural Capability measurement Tool reflected the core cultural capabilities of The Framework. The draft tool appears suitable for use with midwifery students.